2017
DOI: 10.1007/s00213-017-4534-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of antipsychotic and propsychotic drugs on prepulse inhibition and locomotor activity in Roman high- (RHA) and low-avoidance (RLA) rats

Abstract: Rationale Animal models with predictive and construct validity are necessary for developing novel and efficient therapeutics for psychiatric disorders. Objectives We have carried out a pharmacological characterization of the Roman high-(RHA-I) and low-avoidance (RLA-I) rat strains with different acutely administered propsychotic (DOI, MK-801) and antipsychotic drugs (haloperidol, clozapine), as well as apomorphine, on prepulse inhibition (PPI) of startle and locomotor activity (activity cages). Results RHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 85 publications
(152 reference statements)
2
17
0
Order By: Relevance
“…In line with these strain-related differences in LI, we have shown in a series of studies that RHA rats display clear and consistent deficits of PPI of the acoustic startle response compared with RLAs (Del Rio et al, 2014; Oliveras et al, 2015, 2016, 2017; Río-Alamos et al, 2015; Río-Álamos et al, 2017a,b, 2019; Tapias-Espinosa et al, 2018, 2019) and that PPI deficits predict spatial working memory impairments (Oliveras et al, 2015). Altogether, the above mentioned cognitive and attentional profiles of RHA vs. RLA rats suggest that the former may represent a model of schizophrenia-relevant features.…”
Section: Rha Rats As a Model Of Deficits In Attentional Processes Cosupporting
confidence: 53%
See 2 more Smart Citations
“…In line with these strain-related differences in LI, we have shown in a series of studies that RHA rats display clear and consistent deficits of PPI of the acoustic startle response compared with RLAs (Del Rio et al, 2014; Oliveras et al, 2015, 2016, 2017; Río-Alamos et al, 2015; Río-Álamos et al, 2017a,b, 2019; Tapias-Espinosa et al, 2018, 2019) and that PPI deficits predict spatial working memory impairments (Oliveras et al, 2015). Altogether, the above mentioned cognitive and attentional profiles of RHA vs. RLA rats suggest that the former may represent a model of schizophrenia-relevant features.…”
Section: Rha Rats As a Model Of Deficits In Attentional Processes Cosupporting
confidence: 53%
“…It is noteworthy that PPI of the acoustic startle is further impaired by the non-selective DA D1/D2 receptor agonist apomorphine and improved by the DA D2/D3 receptor antagonist haloperidol in RHAs but not RLA rats (Oliveras et al, 2017).…”
Section: Rha Rats As a Model Of Deficits In Attentional Processes Comentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, recent data (Oliveras et al, 2017) also shows a difference in responsiveness of the RHA and RLA strains to antipsychotic drug treatment. Oliveras et al (2017) revealed that only the RHA rats are responsive to the typical antipsychotic haloperidol (Drd2 antagonist) in reducing prepulse inhibition (PPI). The a-typical antipsychotic clozapine did not show any difference in efficiency to reduce PPI between the RHA and RLA strains.…”
Section: Discussionmentioning
confidence: 92%
“…The interaction of glutamatergic and dopaminergic systems in the prefrontal cortex plays a significant role in the mechanisms of attention and executive control (Aquila and Citrome, 2015 ; Storozheva et al, 2015 ). Of note, the results of the animal studies showed relatively independent pathways for the participation of glutamatergic and dopaminergic transmission in the mechanisms of PPI (Keith et al, 1991 ; Callahan et al, 2014 ; Oliveras et al, 2017 ). At the same time, the close interaction of dopaminergic and cholinergic activities on sensory and sensorimotor gating has been documented in several studies (De la Salle et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%